Florida 4-H Livestock Breeding Project Record Book - Nancy Johnson (EDIS)
4-H Livestock Breeding Project Record Book (4H ASM 51) is an animal sciences record book for all members in this project area to keep record of their breeding project. In EDIS this publication is DLN 4H 109. Visit the 4-H Youth Development Curriculum website for more information on related project materials. First published in June 1997.